STRATEGI PENGEMBANGAN PRODUK PEMBIAYAAN SYARIAH KSPPS TERHADAP PENINGKATAN DAYA SAING DI KOPERASI BAKTI HURIA CABANG BONE - Pematasari, widya; Hidayati Darwis, Rahma (Faculty of Islamic Economics and Business, 2022)
This study discusses the strategy of developing sharia financing products for savings and loans cooperatives on sharia financing towards increasing competitiveness (KSPPS). KSPPS in performing its function is to collect, manage and distribute and distribute funds. The method used in this study is qualitative research as for the influence in the background with interview and documentation methods. The results of this study show that, the Sharia financing product system with a mudhÄrabah contract at the KSPPS Bakti Huria Bone Branch Cooperative, the existing financing is financing used to help the community which is carried out in the form of deposits and loans by making contracts in accordance with sharia principles. The level of competitiveness in the KSPPS Bakti Huria Bone Branch Cooperative must be gradual, meaning that the increase in competitiveness begins with efforts to win the competition. To find out the various conditions of competitiveness of cooperatives, a form of continuous development is needed, in order to improve the standard of living for cooperatives in the community. the strategy of increasing competitiveness in the KSPPS Bakti Huria Bone Branch Cooperative is through approaches, services and strategies for members of the KSPPS Bakti Huria Bone Branch Cooperative by conducting its payment system via online, namely through an application (member) and it does not stop there also the KSPPS Bakti Huria Bone Branch Cooperative teaches its members how to manage the money lent to members and assist in the business process.